Blue Economy Challenge The Threatening Impact of Indonesia’s Sea Sand Export Policy - Wahyudi, Mhd Andika (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This research discusses the Indonesian government’s sand export policy and its relationship to the challenges of the Blue Economy. The sand export policy is regulated in Government Regulation Number 26 of 2023, it is feared that the policy will have a negative impact on the environment and society. Through descriptive qualitative methods, this research discusses the history of Indonesian sea sand exports, their impacts and their relationship as an obstacle to the blue economy. The findings of this research show that there is a threat of damage to the marine environment and coastal areas, which has a negative impact on the economy of local communities. In the future, it is hoped that this research can be developed with various other indicators and concrete case studies as well as further connections to the Blue economy